Efficiency enhancement of natural cocktail dyes in a TiO2-based dye-sensitized solar cell and performance of electron kinetics on the TiO2 surface - Dhanasekaran, P.; Marimuthu, R. (Frontiers in Energy Research, 2023)
In the present study, natural dyes extract prepared from the dried leaves of Andrographis Paniculata and Psidium Guajava (APPG). The objective of this study is to increase the light harvesting phenomenon from solar energy by utilizing natural dye from APPG and the problem statement is to harvest the optimum solar radiation and convert it into electrical energy. Acetone and Ethanol were used as solvents during the preparation process. By this research conducted, the crystallite size of TiO2 nanoparticles was assessed, the impact of acetone and ethanol on APPG dye was compared and the absorption spectra, FTIR spectra and UV-Vis spectra of the solar cell fabrication process using solvents were experimentally explored. The APPG leaf extract functions as a dye sensitizer. The cells are precisely sandwiched with photoanode, TiO2 nanoparticles, electrolyte (I/I3-), and cathode. JV properties of dye extracts utilising acetone and ethanol were measured using a solar simulator equipped with a 100 mW/cm2 Xenon light and a Keithley 2400 Graphical Series SMU. An experimental DSSC with dye extraction utilizing Acetone solvent yielded a maximum photo-conversion efficiency of 0.6914%, whilst ethanol yielded a photo-conversion efficiency of 0.5630%. Furthermore, an energy level diagram was used to explain the electron kinetics process of DSSC, and it was discovered that the time required to transfer electron injection in TiO2 surface from a dye-excited state is 150 ps.